Quest to enhance up-conversion efficiency: a comparison of anhydrous vs. hydrous synthesis of NaGdF4: Yb3+ and Tm3+ nanoparticles. (September 2020) - Purohit, B.; Amans, D.; Guyot, Y.; Mahler, B.; Joubert, M.-F.; Dujardin, C.; Daniele, S.; Ledoux, G.; Mishra, S.
Abstract: A major challenge in the field of up-converting (UC) nanomaterials is to enhance their efficiencies. The –OH defects on the surface of the nanoparticles are thought to be the main cause of luminescence quenching, but there are no comparative studies in the literature showing the impact of anhydrous vs. hydrous synthesis on up-conversion efficiency. In this article, we present the synthesis of up-converting NaGdF4 : Yb +3, Tm +3 nanoparticles by two different methods: thermal decomposition of single source metal-organic anhydrous precursors [NaLn(TFA)4 (diglyme)] (Ln = Gd, Tm, Yb; TFA = trifluoroacetate) and room temperature co-precipitation using hydrated inorganic salts Ln(NO3 )3 ·5H2 O (Ln = Gd, Tm, Yb), NaNO3 and NH4 F in ethylene glycol. After a detailed study on the influence of solvents and the percentage of lanthanide dopant on the crystal phase of the up-converting nanoparticles (NPs) and their complete characterization, a comparative up-conversion study was carried out which revealed that the uniform nanospheres (av. size ∼13 nm) obtained from the anhydrous SSP had significantly higher up-conversion efficiency than agglomerated nanorods (∼197 nm in length and ∼95 nm in width) produced from hydrated inorganic salts. An enhanced up-conversion quantum yield of 1.8% for the anhydrous sample validates the anhydrous precursor approach as a strategy to obtain small but highly emitting up-converting particles without requiring a silica or undoped matrix surface passivation layer. Graphical abstract: Image 1 Highlights: Synthesis of NaGdF4 :Yb 3+, Tm 3+ NPs by i) thermal decomposition of anhydrous precursors and ii) co-precipitation of hydrated inorganic salt. Selective access to pure α-, pure β- or mixed α + β crystalline phases with defined ratios. Significantly enhanced up-conversion efficiency by using anhydrous conditions.